Traditional foods of the popular cuisine in Salinas-Guaranda as a potential culinary tourist destination - Guevara Aroca, Francisco Xavier; Aldaz Chicaiza, Jessica Susana; Buenaño Allauca , Monica (SATHIRI, 2023)
It began with the observation in the field (territory) where a possible loss of food cultural identity was identified, evidenced in the culinary offer of restaurants in the area and the lack of knowledge of the new generations in relation to their popular cuisine. Therefore, it was stablished as an objective to analyze the food customs and traditions of the Salinas town (territory / village), in order to value the culinary tradition through the structuring and documentary organization of the identified customs. With the intention of becoming a resource for culinary tourism in the sector, the methodology was qualitative and exploratory. Information was gathered through interviews with local knowledge holders between 60 and 91 years of age. The knowledge transmitted was codified through recipes of traditional popular cuisine and finally reproduced with typical culinary techniques and local products. The research allowed to identify that the food manifestations of the sector can still be found in the different stages of the year related in turn to indigenous and mestizo rites and festivities. And indigenous and mestizo festivities with slight modifications due to gastronomic globalization. Therefore, it is conclude that through adequate tourism management it is possible to generate economic and social development based on cultural expressions, both food and other types that exist in Salinas – Guaranda, based on a creative tourism that strengths the identities of the locality.
Keywords: Traditional cuisine; Territory; food manifestations; culinary knowledge; culinary tourism